Education and communication to increase public understanding of nuclear technology peaceful uses (Brazilian Journal of Radiation Sciences (BJRS), 2015)
Nuclear technology helps to improve the quality of our everyday life. Nevertheless, there is still great misinformation and the issue divides public opinion. Several surveys were conducted over the past years to study public acceptance of Nuclear Technology in Brazil and worldwide. GlobeScan (2005), for the International Atomic Energy Agency (IAEA), and Eurobarometers (2010), published by the Nuclear Energy Agency (NEA) and the Organization for Economic Co-operation and development (OECD),  report similar socio-demographic trends: the higher the education level, the more favorable is public opinion towards nuclear power. Taking into account education and communication are crucial to increase public knowledge and understanding of the benefits of Nuclear Technology and that Internet access has increased strongly all over the country, this educational project aims to take advantage of the potential of Information and Communication Technology (ICT) to disseminate the peaceful use of nuclear technology and its benefits, informing children and teenagers, as well as parents and teachers, who are most often unaware of the matter. Whereas Internet access has increased strongly for both public and private schools all over the country, this web-based educational project, entitled Radioatividades (Radioactivities), provides short courses, curiosities and interactive activities covering topics related to Nuclear Technology and its beneficial applications in several areas, such as medicine, agriculture, industry, art and electric power generation. The project uses the combination of multiple technologies and last generation internet resources. Our target is the dissemination of information, promoting the benefits of Nuclear Technology for new generations, contributing to public acceptance of Nuclear Technology, combating misinformation in our society, omission of the media and knowledge fragmentation. Education transforms old prejudices and inspires new thoughts, stimulating development and encouraging scientific and technological research.